Lipid and Protein Content in Rainbow Trout in Relation to Gonadal Growth - Bhat, Rayees Ahmad; Saoca, Concetta; Arfuso, Francesca; Pino, Carmelo; D’alessandro, Enrico; Zumbo, Alessandro; Fazio, Francesco; Kesbiç, Osman Sabri (Walter de Gruyter GmbH, 2022)
Abstract The purpose of this study was to examine various lipid classes as well as the protein content in rainbow trout ovaries. A total of 80 samples of Oncorhynchus mykiss (Walbaum 1792) were collected from Kokernag and Verinag hatcheries (Jammu and Kashmir, India) between 2017 and 2019. The mature stage in female fish had the highest gonadosomatic index (GSI) and minimal GSI in the spent stage. Higher lipid content of the ovary was reported during the mature stage (36%), as compared to other pre-breeding stages. Similarly, lipid classes also showed fluctuation during the development of the ovary. The lipid classes, i.e. glycolipids, free fatty acids, cholesterol and triglycerides, had a higher content in the mature stage, while the phospholipid content was higher in the mature stage. The protein content was also higher in the mature ovary than in the other developmental stages. The study provides reference values for various biochemical parameters in rainbow trout that could be useful for population monitoring programs and for the development of diets and management methods for fish production under controlled conditions.
Keywords: glycolipids; SH1-691; rainbow trout; proteins; lipid; fish ovaries; Aquaculture. Fisheries. Angling; Rainbow trout, Lipid, Fish ovaries, Glycolipids, Breeding season, Proteins; breeding season; 14. Life underwater